El discurso oral en la cosecha de la yuca: shima shima, el caso asháninka - Quinchisa Cárdenas, Celestino (2025)
This article analyzes the ritual discourse that takes place at the time of harvesting cassava. The harvest is largely carried out by women, with great respect and care for the ancestral food that is present in food and drink. The objective of this study is to describe the ritualized discourse that is practiced duringthe harvest of the tuber known as cassava so that this cultural knowledge is not lost. The methodology used is qualitative, ethnographic, focusing on the cultural practices ritualized in the harvest. The technique used is non-participant observation, the unstructured interview where the researcher uses the Asháninka language in spontaneous conversations with the wise women. The result of the research indicates that the ritual discourse “akamitero kaniri”, is an act of petition through body movement, repeating the metaphorical words in Asháninka to have a good harvest.